2004
DOI: 10.1007/s10126-003-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Telomerase Activity in Tissues and Primary Cultured Lymphoid Cells of Penaeus japonicus

Abstract: Telomerase is a ribonucleoprotein enzyme that can elongate telomeric DNA, which is thought to be required for the development of cellular immortality and oncogenesis in mammals. We examined telomerase activity in tissues and primary cultured lymphoid cells of adult penaeid shrimps. Using the telomeric repeat amplification protocol (TRAP), we studied the characteristics of a putative novel telomerase in Penaeus japonicus. This telomerase could be inactivated by heating or treatment with RNase A or proteinase K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
1
19
2
Order By: Relevance
“…In our study (un-published data) we could not find any telomerase activity in primary lymphoid cell culture using telomeric repeat amplification protocol assay. Even though, this is contradictory to the reported active telomerase activity in cultured lymphoid organ cells for up to 30 days [47], till date, no additional report has been seen in literature to confirm the telomerase activity in the cultured shrimp cells.…”
Section: Molecular Approaches For Shrimp Cell Immortalizationcontrasting
confidence: 76%
See 1 more Smart Citation
“…In our study (un-published data) we could not find any telomerase activity in primary lymphoid cell culture using telomeric repeat amplification protocol assay. Even though, this is contradictory to the reported active telomerase activity in cultured lymphoid organ cells for up to 30 days [47], till date, no additional report has been seen in literature to confirm the telomerase activity in the cultured shrimp cells.…”
Section: Molecular Approaches For Shrimp Cell Immortalizationcontrasting
confidence: 76%
“…Of the 50 selected publications, 17 reported (34 %) P. monodon [2-4, 7, 8, 10, 15, 23, 35, 41, 42, 44, 58, 69, 83, 89, 90] as the species of choice, eight researchers (16 %) used Penaeus japonicus [10,39,47,48,[55][56][57]72], seven (17 %) selected Penaeus chinensis [13, 19, 36-38, 40, 80] and Penaeus vannamei [18,26,27,49,51,63,82]. Moreover, six authors (16 %) selected Penaeus stylirostris [49,51,63,73,74,78] as the donor animal of tissues and organs.…”
Section: Species Of Choice: a Major Concernmentioning
confidence: 99%
“…With each cell division, telomeres shorten due to the inability of DNA polymerases to replicate the ends of linear DNA molecules (Morin 1997;Nakamura et al 1997) and when telomeres reach a critical length, cells enter a non-dividing stage termed senescence (Harley et al 1990;Cerni 2000;Lang et al 2004). Further, the role of telomere shortening in cellular senescence has been observed in different cell lineages (Harley et al 1990; Allsopp et al 1992), and confirmed that immortalized cells should have telomerase activity and stable telomeres (Kim et al 1994;Harley 1991;Olovnikov 1973).…”
Section: Introductionmentioning
confidence: 82%
“…Like vertebrates (Forsyth et al 2002) and plants (Fitzgerald et al 1996), the distribution of telomerase activity has been studied in insects (Sasaki and Fujiwara 2000) and other invertebrates including sponges (Koziol et al 1998), lobster (Klapper et al 1998a), shrimps (Lang et al 2004), molluscs (Owen et al 2007), sea squirts (Sköld et al 2011) corals and algae (Zielke and Bodnar 2010). Subsequent to the detection of telomerase activity by Lang et al (2004) in Penaeus japonicus, there has been no further studies in this direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation